2012
DOI: 10.1002/ijc.27514
|View full text |Cite
|
Sign up to set email alerts
|

Development of gastric cancer in nonatrophic stomach with highly active inflammation identified by serum levels of pepsinogen and Helicobacter pylori antibody together with endoscopic rugal hyperplastic gastritis

Abstract: This study aimed to elucidate groups at high risk of developing cancer among patients with serologically identified Helicobacter pylori infection and nonatrophic stomach. Annual endoscopy was performed for a mean of 5.4 years in 496 asymptomatic middle-aged men who were H. pylori antibody-positive and pepsinogen (PG) test-negative. Subjects were stratified according to the activity of H. pylori-associated gastritis measured by serum levels of PG and H. pylori antibody, and/or by endoscopic findings of rugal hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
82
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 92 publications
(89 citation statements)
references
References 45 publications
4
82
1
2
Order By: Relevance
“…In contrast, diffuse-type cancer develops in the stomach following chronic active inflammation without passing through the intermediate steps of atrophic gastritis or intestinal metaplasia. Of particular note, the activity of mucosal inflammation is proposed for a risk of diffuse-type cancer [9,10,38]. To date, studies about DNA methylation in gastric carcinogenesis have been mainly focused on the intestinal type [22,23,28,39].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, diffuse-type cancer develops in the stomach following chronic active inflammation without passing through the intermediate steps of atrophic gastritis or intestinal metaplasia. Of particular note, the activity of mucosal inflammation is proposed for a risk of diffuse-type cancer [9,10,38]. To date, studies about DNA methylation in gastric carcinogenesis have been mainly focused on the intestinal type [22,23,28,39].…”
Section: Discussionmentioning
confidence: 99%
“…There have been efforts to identify these subgroups, actually Kiyohira et al [18] showed gastritis severity and gastric mucosal status could be well documented by serum PG. Recent Japanese studies [1,19] uncovered some groups of atrophy free subject showed GC risk equivalent to extensive atrophic gastritis especially diffuse type GC, the main characteristics of these subgroups were elevated PG II. Considering Hunter et al [20] that H.pylori infection contribute more to PG II elevation than to PG I, and Iranian study [21] suggesting that PG II could be good surrogate marker for body morphological change after H.pylori infection, and major portion of PG II was originated from the active gastritis by neutrophil cell infiltration, we could come to conclusion that H.pylori infected active gastritis creating more neutrophil infiltration would cause more PG II elevation.…”
Section: Discussionmentioning
confidence: 99%
“…and actually when we made the protocol we referred to watanabe et al [27] reporting that all cancers in high H.pylori titer group belonged to Group B-γ, inevitably some portion of active gastritis subjects in Group B might be omitted and performing genuine Korean active gastritis study would be the way to go. Because we depend on CLO test for H.pylori identification, some H.pylori positive subjects might be exempted from the study, however we used EAB and various endoscopic findings: we must have tried to find out H.pylori by other methods if we had confronted abnormal mucosal findings with negative CLO test (actually all of four subjects who showed no visible EAB had abnormal mucosal patterns), consequently most of the exempted cases might be Group D not Group B and thinking of our main purpose they would not be considered as candidate for primary GC prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Watanabe et al 1 have recently described development of gastric cancers of Laurens diffuse type in patients with rugal hyperplastic (enlarged fold) gastritis, all located in the gastric corpus. We have read their publication with interest.…”
Section: Dear Editormentioning
confidence: 99%
“…4 Furthermore, gastric carcinomas of the diffuse type in patients with atrophic gastritis have neuroendocrine differentiation and have been suggested to develop from ECL cells. 5 Altogether, there is a large number of studies suggesting that gastrin may be pivotal for gastric mucosal hyperplasia and carcinogenesis and serum gastrin should have been measured in the study by Watanabe et al 1 The serum concentrations of PGs do not necessarily reflect gastric acidity or degree of atrophy and particularly some persons with reduced gastric acid secretion and, thus, presumed hypergastrinemia may have serum PGI in the normal range. 6,7 Yours sincerely, Reidar Fossmark and Helge Waldum…”
Section: Dear Editormentioning
confidence: 99%